Nanometer composite tungsten-based alloy and preparation method thereof

By introducing nano-scale enhanced phases and optimization processes into tungsten-based alloys, the problem that tungsten-based alloys are difficult to maintain high strength and oxidation resistance at the same time in high temperature environments is solved, and the balance of high strength, toughness and oxidation resistance is achieved, meeting the needs of high-end applications and optimizing production efficiency.

CN119736534APending Publication Date: 2025-04-01YANGTZE RIVER DELTA PHYSICS RES CENT CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411963346.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

It is difficult for existing tungsten-based alloys to maintain high strength and good oxidation resistance at the same time under high temperature environments. The traditional preparation process causes defects such as uneven powder mixing, abnormal grain growth, and easy cracks to occur during forging, which limits the further improvement of alloy performance.

Method used

The preparation method of nanocomposite tungsten-based alloy is adopted to adjust the content and particle size of alloy elements, and nano-scale reinforced phases such as silicon carbide and aluminum nitride are introduced to regulate the structure, hinder dislocation movement, and improve strength and toughness. Specific processes include multi-stage powder mixing, cold isostatic pressure, low-temperature activated sintering, forging, annealing and low-temperature aging treatment.

Benefits of technology

It achieves a high strength and high toughness balance of tungsten-based alloy in high temperature environments, improves the oxidation resistance and overall performance of the alloy, meets the application needs of high-end fields such as aerospace, and optimizes process parameters, improves production efficiency and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736534A_ABST
    Figure CN119736534A_ABST
Patent Text Reader

Abstract

The invention provides a nano composite tungsten-based alloy. The alloy comprises the following components in parts by weight: 84.0 to 87.0 parts of W powder, 7.0 to 9.0 parts of N powder, 3.0 to 5.0 parts of Fe powder, 0.2 to 0.5 part of Co powder, 1.5 to 2.5 parts of Mo powder, 0.8 to 1.0 part of Zr powder, 0.5 to 0.8 part of Cr powder, 0.3 to 0.5 part of Mn powder, 0.4 to 0.5 part of B powder, 0.2 to 0.4 part of Ta powder, 0.1 to 0.3 part of Hf powder, 0.1 to 0.2 part of V powder, 0.1 to 0.3 part of T powder, 0.1 to 0.2 part of silicon carbide powder, 0.1 to 0.2 part of aluminum nitride powder, 0.3 to 0.5 part of yttrium oxide powder and 0.1 to 0.2 part of lanthanum oxide powder. The yield strength of the nano-composite tungsten-based alloy can reach 1270-1520 MPa, the tensile strength of the nano-composite tungsten-based alloy is 1430-1680 MPa, the ductility of the nano-composite tungsten-based alloy is 6-12%, and the impact toughness of the nano-composite tungsten-based alloy is 130-220 J / cm < 2 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of alloys, and in particular relates to a nano composite tungsten-based alloy and a preparation method thereof. Background Art

[0002] Tungsten-based alloys play a vital role in high-end application fields such as aerospace, national defense and military industry due to their excellent high-temperature performance, high density and high strength. However, tungsten-based alloys in the existing technology have obvious deficiencies in composition design and preparation process, especially in high-temperature environments, and it is difficult to maintain high strength and good oxidation resistance at the same time. In addition, defects such as uneven powder mixing, abnormal grain growth, easy cracking during forging, and the inability of annealing process to effectively eliminate residual stress caused by traditional preparation processes have limited the further improvement of alloy performance.

[0003] In particular, traditional tungsten-based alloys often sacrifice toughness while pursuing high strength, which makes the alloy prone to brittle fracture when subjected to impact loads or complex stress states. On the contrary, if the focus is on improving toughness, strength may be sacrificed to a certain extent, and the requirements of high-strength application scenarios may not be met. This contradictory relationship between strength and toughness limits the application of tungsten-based alloys in modern high-end fields. Summary of the invention

[0004] In view of this, the present invention aims to overcome the defects in the prior art and proposes a nano-composite tungsten-based alloy and a preparation method thereof.

[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] The present invention provides a nanocomposite tungsten-based alloy, which comprises the following components in parts by weight:

[0007] W powder: 84.0-87.0 parts, Ni powder: 7.0-9.0 parts, Fe powder: 3.0-5.0 parts, Co powder: 0.2-0.5 parts, Mo powder: 1.5-2.5 parts, Zr powder: 0.8-1.0 parts, Cr powder: 0.5-0.8 parts, Mn powder: 0.3-0.5 parts, B powder: 0.4-0.5 parts, Ta powder: 0.2-0.4 parts, Hf powder: 0.1-0.3 parts, V powder: 0.1-0.2 parts, Ti powder: 0.1-0.3 parts, silicon carbide powder: 0.1-0.2 parts, aluminum nitride powder: 0.1-0.2 parts, yttrium oxide powder: 0.3-0.5 parts, lanthanum oxide powder: 0.1-0.2 parts.

[0008] Furthermore, the mass ratio of the silicon carbide powder (SiC) to the lanthanum oxide powder (La2O3) is 1:0.6-0.9. By introducing nano-scale reinforcing phases, silicon carbide and aluminum nitride, the organizational structure of the alloy is regulated on a microscopic scale, dislocation movement is effectively hindered, and toughness is improved while strength is increased. When SiC and La2O3 are added in this ratio, the two form a synergistic effect, which has an important impact on the strength and toughness balance of the alloy. Within this ratio range, as the La2O3 content changes, its purification and strengthening effect on the grain boundary cooperates with the strengthening effect of SiC on the matrix, so that when the alloy is subjected to external force, it can not only effectively hinder dislocation movement and improve strength, but also improve toughness by optimizing the grain boundary structure and inducing a variety of deformation mechanisms.

[0009] Furthermore, the sum of the masses of the Ti powder, Ta powder and Co powder accounts for 0.7-0.95% of the alloy. Ti, Ta and Co work together in the alloy, which is crucial to the optimization and improvement of the overall performance of the alloy. Ti can form stable compounds with other elements to strengthen the grain boundaries, improve strength, toughness and corrosion resistance; Ta, as a high melting point metal element, improves the high temperature stability and corrosion resistance of the alloy; Co promotes the uniform diffusion of alloy elements, improves crystallization uniformity, enhances organizational stability, and affects the formation and distribution of carbides and nitrides. Within this content range, the alloy can meet the diverse performance requirements under different working conditions. For example, under high temperature and high stress conditions such as the hot end components of aerospace engines, this ratio can make the alloy have good creep resistance, and the deformation is small when subjected to high temperature loads for a long time, ensuring the reliability and service life of the components.

[0010] Further, the Fischer-Strauss particle size of the W powder is 2.0-4.0 μm; the Fischer-Strauss particle size of the Ni powder is 2.0-4.0 μm; the Fischer-Strauss particle size of the Fe powder is 5.0-8.0 μm; the Fischer-Strauss particle size of the Co powder is 1.0-3.0 μm; the Fischer-Strauss particle size of the Mo powder is 2.0-5.0 μm; the Fischer-Strauss particle size of the Cr powder is 1.5-4.0 μm; the Fischer-Strauss particle size of the Mn powder is 5.0-6.0 μm; the Fischer-Strauss particle size of the B powder is 1.5-3.0 μm ; The Fischer particle size of the Ta powder is 0.5-1.0 μm; The Fischer particle size of the Hf powder is 0.5-1.0 μm; The Fischer particle size of the V powder is 1.0-2.0 μm; The Fischer particle size of the Ti powder is 1.0-2.0 μm; The Fischer particle size of the silicon carbide powder is 50-200 nm; The Fischer particle size of the aluminum nitride powder is 50-200 nm; The Fischer particle size of the yttrium oxide powder is 2.0-4.0 μm; The Fischer particle size of the lanthanum oxide is 2.0-4.0 μm. The present invention achieves optimized synergy between elements by adjusting the content and particle size of the alloy elements, thereby further improving the comprehensive performance of the alloy.

[0011] The present invention also provides a method for preparing a nanocomposite tungsten-based alloy, comprising the following steps:

[0012] (1) putting each component into a multi-stage powder mixing device for preliminary mixing to obtain a mixed powder;

[0013] (2) placing the mixed powder into an elastic mold for cold isostatic pressing to obtain a rod blank;

[0014] (3) The rod blank is subjected to low-temperature activation sintering, forging, annealing, and low-temperature aging treatment to obtain the nano-composite tungsten-based alloy.

[0015] Furthermore, the rotation speed of the multi-stage powder mixing equipment in step (1) is 1000-1500 rpm, the vibration frequency is 10-20 Hz, and the time is 8-15 hours.

[0016] Furthermore, the pressure of the cold isostatic pressing step in step (2) is 150-250 MPa, and the holding time is 5-10 min.

[0017] Furthermore, the low-temperature activated sintering step in the step (3) is assisted by ultrasound, the frequency of the ultrasound is 35-75kHz, the power is 1.5-4kW, the time of the heating stage is 1.5-2.5h, the time of the insulation stage is 2-3h, and the time of the cooling stage is 0.5-1h; the temperature of the low-temperature activated sintering step is 1050-1250°C, the time is 4-6h, the heating rate is 8-12°C / min, the activator is yttrium oxide or lanthanum oxide, and the amount of the activator added is 1-2.5wt%.

[0018] Furthermore, the temperature of the forging step in step (3) is 450-900°C, the heat preservation time is 0.8-2.2h, the forging passes are 3-5 times, and the forging amount each time does not exceed 25%; the temperature of the low-temperature aging treatment step in step (3) is 200-300°C, and the heat preservation time is 1-2h.

[0019] Furthermore, the annealing step in step (3) includes preheating treatment and vacuum pulse annealing; the preheating temperature is 300-400°C, and the preheating time is 0.5-1h; the vacuum pulse annealing includes heating annealing and pulse cooling process; the vacuum degree of heating annealing is 10 -4 -10 -5Pa; the heating process of vacuum pulse annealing is divided into the following stages: heating from room temperature to 600℃, with a heating rate of 5-8℃ / min; heating from 600℃ to 900℃, with a heating rate of 8-12℃ / min; heating from 900℃ to 1050-1150℃, with a heating rate of 6-10℃ / min; a 10-15min constant temperature platform period is set at the end of each heating stage; the cooling process of vacuum pulse annealing adopts pulse cooling method: when cooling to 700℃, first quickly cool to 800℃, with a cooling rate of 8-10℃ / min, keep for 5-10min, and then slowly cool to 700℃, with a cooling rate of 3-5℃ / min; when cooling from 700℃ to 300℃, first quickly cool to 500℃, with a cooling rate of 6-8℃ / min, and then slowly cool to 300℃, with a cooling rate of 2-4℃ / min; finally cool from 300℃ to room temperature, with a cooling rate of 5-8℃ / min, and a vacuum degree of 10 -5 -10 -6 Pa and maintain for 3-5min.

[0020] The preliminary mixing step of the preparation method of the nano-composite tungsten-based alloy adopts a multi-stage powder mixing device, which combines the principles of high-speed rotation and low-frequency vibration to improve the powder mixing effect. The powder is first preliminarily mixed in the high-speed rotation area to break the agglomeration, and then enters the low-frequency vibration area to further improve the uniformity and promote the uniform distribution of the element powder. Compared with the traditional ball mill mixer (which requires 12-24h mixing time), this method significantly shortens the mixing time to 8-15h, and has a better mixing effect, which improves the quality and performance consistency of the alloy and provides high-quality powder raw materials for subsequent processes.

[0021] The cold isostatic pressing step sets the cold isostatic pressing pressure to 150-250MPa, and the holding time is controlled at 5-10min. Under this pressure and holding time, the gaps between the powder particles can be effectively compacted, so that the density of the green body is significantly improved, and the green body density can reach 70-80% of the theoretical density, providing a green body foundation with more uniform density and more compact structure for the subsequent sintering process, which helps to further improve the overall performance of the final tungsten-based alloy.

[0022] The sintering step adopts a method combining ultrasonic assistance and low-temperature activation sintering to ensure material diffusion and reaction; the temperature reduction stage releases stress evenly to reduce defects.

[0023] The temperature control of the low-temperature activation sintering step fine-tunes the ultrasonic parameters during the heat preservation stage and plays the role of an activator.

[0024] The forging step adopts an intelligent forging system to automatically and accurately adjust the forging force and speed according to the real-time temperature, stress and other parameters of the alloy billet. Compared with the forging of the traditional precision forging machine, the system has better controllability, can improve the quality and performance of the alloy, reduce forging defects, and ensure uniform and dense internal structure. During the forging process, the temperature measurement accuracy of the real-time monitoring system can reach ±5°C, the stress measurement accuracy can reach ±5MPa, the forging force adjustment accuracy can reach ±5kN, and the forging speed adjustment accuracy can reach ±0.05m / s.

[0025] The annealing steps include heat treatment and vacuum pulse annealing; preheating reduces thermal stress and creates favorable conditions for subsequent annealing; vacuum pulse annealing is performed in a high vacuum environment, and the heating process is controlled in stages; a constant temperature platform period is set at the end of each heating stage to ensure the homogenization of the alloy structure; the cooling process adopts a pulse cooling method: the vacuum degree is periodically increased during the entire annealing process to promote the discharge of gas impurities and improve the purity and performance of the alloy.

[0026] The low-temperature aging treatment is carried out at 200-300°C, and heat preservation is performed to further stabilize the alloy structure, significantly improve its stability, and ensure the excellent long-term performance of the alloy.

[0027] The functions of the components of the nanocomposite tungsten-based alloy described in the present invention are as follows:

[0028] W powder: As a core matrix element, it provides a high melting point, high density and high strength basic framework, carries other elements to play their roles, and lays the foundation for the basic performance of the alloy in high temperature and high strength application scenarios.

[0029] Ni powder: As the main bonding phase element, it effectively improves the toughness of the alloy, allowing the alloy to absorb energy through plastic deformation when impacted by external forces, avoiding brittle fracture, improving processing performance, reducing processing difficulty, and facilitating the forming and processing of complex shapes.

[0030] Fe powder: It forms a bonding phase together with Ni powder, optimizes the organizational structure, enhances the bonding force between different internal phases, improves the overall mechanical properties, and enables the alloy to disperse stress more evenly when subjected to load.

[0031] Co powder: As a necessary added element, it can promote uniform diffusion of alloy elements, improve crystallization uniformity, and enhance organizational stability. It works together with Ni, Fe and other bonding phase elements to optimize the bonding phase microstructure, improve the bonding phase strength and toughness, and thus improve the overall mechanical properties of the alloy. At the same time, it affects the formation and distribution of carbides and nitrides in the alloy, refines these second phase particles, makes them more evenly distributed in the matrix, and further strengthens the alloy. In high temperature and high stress environments, it helps to improve creep resistance, allowing the alloy to maintain a small deformation when subjected to high temperature loads for a long time, thereby improving reliability and service life.

[0032] Mo powder: It reduces the density of tungsten alloy, which is more advantageous in applications with weight requirements (such as aerospace components). It also greatly enhances the high-temperature strength (such as maintaining good mechanical properties under high-temperature conditions above 1000°C) without significantly sacrificing strength, effectively resists high-temperature creep deformation, and extends service life.

[0033] Zr powder: refines the grain structure, inhibits grain growth, and makes the grains small and uniform. Fine grains hinder dislocation movement, improve strength and toughness, and disperse stress through more grain boundaries and internal deformation mechanisms when the alloy is subjected to stress, avoiding stress concentration and cracks.

[0034] Cr powder: Improves oxidation resistance, forms a continuous and dense oxide film on the alloy surface, prevents oxygen intrusion, slows down the oxidation process, protects the matrix, and cooperates with other elements to enhance chemical and structural stability, ensuring stable performance in complex environments.

[0035] Mn powder: plays an important role in the alloy processing process, reducing the deformation resistance during cutting, forging and other processing processes, reducing the generation of processing cracks, improving the processing surface quality, and facilitating the acquisition of precise size and shape.

[0036] B powder: It is concentrated at the grain boundary to fill defects, enhance the bonding strength of the grain boundary, interact with other elements to optimize the chemical composition and structure of the grain boundary, significantly enhance the ability of the grain boundary to resist crack propagation, and improve the overall toughness and reliability.

[0037] Ta powder: As a high melting point metal element, it improves the high temperature stability of the alloy, enables the alloy to maintain good organizational structure and mechanical properties in high temperature environment (such as the hot end component environment of aerospace engines), and at the same time enhances corrosion resistance and protects the matrix from erosion by corrosive media.

[0038] Hf powder: Similar to Ta element, it improves high-temperature oxidation resistance, forms a stable oxide film at high temperature, prevents oxygen from reacting with the inside of the alloy, refines grains, optimizes microstructure, improves strength and toughness, and has outstanding mechanical properties, especially under high temperature conditions.

[0039] V powder: refines grains, inhibits grain growth, forms a finer and more uniform grain structure, improves strength and toughness, enhances creep resistance, reduces alloy deformation and extends service life under long-term stress (such as high-temperature and high-pressure pipeline components), and is suitable for harsh working conditions such as high temperature and high pressure.

[0040] Ti powder: can form stable compounds with other elements, preferentially distributed at grain boundaries, strengthen grain boundaries, prevent crack initiation and expansion, significantly improve strength and toughness, and can also improve corrosion resistance to a certain extent and improve durability in complex environments.

[0041] Silicon carbide powder: Nano-scale particles are evenly dispersed in the alloy matrix, forming a strong interface bond with the matrix to achieve nano-composite reinforcement effect. It effectively hinders dislocation movement, improves strength, triggers more deformation mechanisms in the matrix (such as dislocation proliferation, grain boundary sliding, etc.), improves toughness, and enables the alloy to achieve a better balance between high strength and high toughness.

[0042] Aluminum nitride powder: As a nano-reinforced phase, it has a good interface with the matrix, improves strength and toughness by hindering dislocation movement and inducing various deformation mechanisms. It also has good thermal stability and thermal conductivity, which helps to improve the thermal stability and heat dissipation performance of the alloy at high temperatures and avoid performance degradation due to local overheating.

[0043] Yttrium oxide (Y2O3): During the solidification and heat treatment of the alloy, it concentrates at the grain boundaries. On the one hand, it adsorbs impurity elements at the grain boundaries, purifies the grain boundary environment, enhances the bonding force of the grain boundaries, prevents cracks from occurring at the grain boundaries, inhibits the initial crack expansion, and significantly improves toughness; on the other hand, it has certain antioxidant properties. Under high temperature conditions, it forms a relatively stable oxide film on the alloy surface, which prevents oxygen from diffusing into the alloy, improves high-temperature antioxidant capacity, enhances stability under high-temperature conditions, and broadens the scope of application.

[0044] Lanthanum oxide (La2O3) powder: It mainly plays the role of purifying grain boundaries, adsorbing impurity atoms at the grain boundaries, reducing the weakening of the impurities on the grain boundary bonding force, affecting the grain boundary migration and atomic diffusion process, improving the organizational structure, making the grain growth more uniform and orderly, comprehensively improving the strength and toughness, and optimizing the overall performance.

[0045] Compared with the prior art, the present invention has the following advantages:

[0046] The nanocomposite tungsten-based alloy of the present invention has a yield strength of 1270-1520 MPa, a tensile strength of 1430-1680 MPa, an elongation of 6-12%, and an impact toughness of 130-220 J / cm 2 Compared with existing competitive products (yield strength 1200-1450MPa, tensile strength 1380-1600MPa, elongation 2-8%, impact toughness 100-190J / cm 2 ), the alloy of the present invention significantly improves toughness and elongation while maintaining high strength, fully meets the strict requirements of high-end fields such as aerospace, national defense and military industry on material properties, and has broad application prospects; at the same time, the optimized process parameters improve production efficiency, reduce production costs, have good market competitiveness, and meet the environmental protection requirements of green manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is the microscopic morphology diagram described in Example 2 of the present invention;

[0048] Figure 2 This is the microscopic morphology image described in Example 9 of the present invention. DETAILED DESCRIPTION

[0049] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0050] The present invention is described in detail below in conjunction with the embodiments.

[0051] 1. Mixing powder

[0052] Use high-precision weighing equipment to mix powder strictly according to the mass percentage of each element.

[0053] 2. Mixed powder

[0054] A new multi-stage powder mixing equipment is used, which combines high-speed rotation with low-frequency vibration. After 8-15 hours of processing, the powder is ensured to be evenly distributed. Compared with traditional ball mill mixers, the mixing time is significantly shortened and the mixing effect is improved.

[0055] 3. Filling powder

[0056] The evenly mixed powder is loaded into the mold, and the powder filling density is enhanced through the ultrasonic vibration loading table, which improves the density and uniformity of the green body and provides a good foundation for subsequent processes.

[0057] 4. Suppression

[0058] Use a cold isostatic press to apply 150-250MPa pressure to the mold and maintain it for a certain period of time, so that the powder particles are tightly combined to form a stable green body, providing quality assurance for sintering.

[0059] 5. Sintering

[0060] The ultrasonic assisted and low temperature activated sintering process is adopted, the ultrasonic frequency is controlled between 35-75kHz, the ultrasonic power is controlled between 1.5-4kW, to promote the fusion of powders. The sintering temperature is 1050-1250℃, the time is 4-6h, and the use of 1.0-2.5% activator can effectively improve the sintering quality and save energy.

[0061] 6. Forging

[0062] The billet is preheated to 450-900℃, and the intelligent forging system is used to adjust the forging force and speed in real time, and the forging passes are controlled to 3-5 times, and the forging amount each time does not exceed 25%. This method helps to improve the grain structure, increase the density of the alloy and reduce forging defects.

[0063] 7. Annealing

[0064] Preheating treatment: Before annealing, preheat at 300-400℃ for 0.5-1h to reduce thermal stress.

[0065] Vacuum pulse annealing: high vacuum (10 -4 -10 -5 Pa) environment. Room temperature to 600℃, 5-8℃ / min heating; 600-900℃, 8-12℃ / min heating; 900℃ to 1050-1150℃, 6-10℃ / min heating, keep constant temperature for 10-15min after each stage. When cooling, 1100℃ drops to 700℃, first cool to 800℃ at 8-10℃ / min and keep for 5-10min, then cool to 700℃ at 3-5℃ / min; 700℃ drops to 300℃, first cool to 500℃ at 6-8℃ / min, then cool to 300℃ at 2-4℃ / min; finally, 300℃ drops to room temperature and cools at 5-8℃ / min. During the annealing process, the vacuum degree is periodically increased to 10 -5 -10 -5 Pa and maintain for 3-5min.

[0066] Low temperature aging treatment: 200-300℃ aging treatment for 1-2h to stabilize the organizational structure.

[0067] 8. Machining

[0068] Wire cutting, grinding machine processing and other means are used to accurately control the size and surface quality of the alloy to ensure that the final product meets the design requirements.

[0069] The chemical compositions and performance results of the embodiments and comparative examples are shown in Table 1.

[0070] Table 1 Chemical composition and performance results

[0071]

[0072]

[0073] In Example 1, the alloy elements are configured in a specific ratio, where W accounts for 85%, Ni accounts for 9%, etc. It exhibits excellent performance, with a yield strength of up to 1520MPa, a tensile strength of 1680MPa, an elongation of 12%, and an impact toughness of 220J / cm 2. W, as a core matrix element, builds a high-strength basic framework and provides support for other elements to play their roles. The bonding phase composed of Ni and Fe cooperates with other elements to achieve an excellent balance between strength and toughness in the alloy. For example, an appropriate amount of Ni effectively improves the toughness of the alloy, so that it can absorb energy through plastic deformation when impacted by external forces to prevent brittle fracture; Mo significantly enhances the high-temperature strength without significantly weakening the strength, ensuring that the alloy maintains good mechanical properties in a high-temperature environment above 1000°C, resists high-temperature creep deformation, and prolongs its service life; trace elements such as Zr, Cr, and Mn and nano-reinforcement phases SiC and Al N work together to refine grains, strengthen grain boundaries, and enhance impact toughness. This embodiment fully demonstrates the excellent performance state that the alloy can achieve under the ideal element ratio and process conditions of the present invention, sets a performance comparison benchmark for the remaining embodiments and comparative examples, and vividly reflects the positive effectiveness of the synergistic effect of each element.

[0074] In Examples 2-4, 7-10, the chemical composition is moderately changed within the scope specified in the invention, such as the fine adjustment of the content of elements such as Ni, Fe, and Mo. Correspondingly, the performance indicators also fluctuate accordingly. Taking Example 3 as an example, its W content is relatively high, reaching 87%, and the Ni and Fe contents are relatively reduced, resulting in a yield strength of 1300MPa, a tensile strength of 1450MPa, an elongation of 11%, and an impact toughness of 190J / cm 2 . Compared with Example 1, the strength is reduced, but the elongation and impact toughness are still maintained at a high level, indicating that although the higher W content affects the strength to a certain extent, the combination of other elements ensures that the toughness is maintained. In Example 7, due to the change in the element ratio, the tensile strength reaches 1600MPa and the elongation is 10.5%, demonstrating the diverse effects of different element combinations on performance. These embodiments jointly confirm that within the scope of the element ratio of the present invention, the alloy performance is adjustable and stable. Even if the element content changes, the alloy can still maintain good comprehensive performance by virtue of the synergistic effect of each element to meet the needs of different application scenarios.

[0075] In Example 5, the mass ratio of SiC to La2O3 is adjusted to 1:0.5, which deviates from the optimal range of 1:(0.6-0.9) specified in the invention. This results in a yield strength of 1320MPa, a tensile strength of 1480MPa, an elongation of 10%, and an impact toughness of 175J / cm 2 Compared with Example 1, both the strength and toughness have declined to a certain extent, which clearly shows that the specific ratio of SiC to La2O3 is crucial to the balance of strength and toughness of the alloy. Deviating from this ratio will interfere with the synergistic effect of the two, thereby affecting the overall performance of the alloy.

[0076] In Example 6, the sum of the contents of Ti, Ta and Co is adjusted to 0.6%, which is lower than the 0.7-0.95% range required by the invention. At this time, the yield strength is 1270MPa, the tensile strength is 1430MPa, the elongation is 12%, and the impact toughness is 200J / cm 2 Compared with Example 1, the strength is significantly reduced, indicating that insufficient Ti, Ta, and Co content will weaken the alloy strengthening effect. Although the elongation and impact toughness are improved, the overall performance is still affected, which strongly emphasizes the key significance of the content of these three elements in optimizing alloy performance.

[0077] Comparative Example 1 does not add nano-reinforced phases SiC and Al N. The absence of nano-reinforced phases (SiC and Al N) results in the lack of strengthening mechanisms such as pinning dislocation movement, grain refinement, and grain boundary purification in the alloy matrix, and fails to induce multiple deformation mechanisms such as dislocation proliferation and grain boundary sliding. The final performance is a yield strength of 1100MPa, a tensile strength of 1300MPa, an elongation of 4%, and an impact toughness of 100J / cm 2 The significant decrease in the nanostructured phase indicates that the nano-reinforcement phase is indispensable in improving the comprehensive performance of the alloy.

[0078] In comparative example 2, no Co element was added, and the alloy properties were significantly reduced, with a yield strength of 1200 MPa, a tensile strength of 1350 MPa, an elongation of 5%, and an impact toughness of 110 J / cm 2 The Co element can promote the uniform diffusion of alloy elements, improve crystallization uniformity, enhance organizational stability, and affect the formation and distribution of carbides and nitrides, which is crucial to improving the overall mechanical properties of the alloy. Lack of Co element will result in insufficient optimization of the microstructure of the bonding phase, resulting in reduced strength and toughness.

[0079] Comparative Example 3 uses the traditional process and has significant performance differences from Example 1. Although the chemical composition of Comparative Example 3 is the same as that of Example 1, due to the poor uniformity of the traditional ball milling powder mixing, high sintering porosity, forging stress concentration and difficulty in eliminating annealing residual stress, the yield strength is 1200MPa, the tensile strength is 1380MPa, the elongation is 3%, and the impact toughness is 115J / cm 2 This further demonstrates the process advantages of the present invention in powder mixing uniformity, sintering density, forging optimization and annealing effect.

[0080] Comparative Example 4 After adjusting the ratio of SiC to La2O3 to 1:1.2, the performance changed, the yield strength was 1300MPa, the tensile strength was 1450MPa, the elongation was 9%, and the impact toughness was 150J / cm 2 Compared with Example 1, the strength and toughness have decreased, which further proves the importance of the synergistic effect of SiC and La2O3 within a specific ratio range on the alloy performance. Departure from this range will lead to performance fluctuations and failure to achieve the optimal state.

[0081] In comparative example 5, the sum of the contents of Ti, Ta and Co is adjusted to 1.2%, which is higher than the required range of the invention. Its yield strength is 1330MPa, tensile strength is 1500MPa, elongation is 7%, and impact toughness is 165J / cm 2 . Compared with Example 1, there are some changes in strength and toughness, indicating that after the content of Ti, Ta, and Co exceeds the optimal range, although the strength is improved, the toughness is reduced, which once again reflects the importance of precise control of the content of these three elements to the comprehensive performance of the alloy. Only within the appropriate content range can a good balance between strength and toughness be achieved. Through in-depth analysis of the embodiments and comparative examples, we can clearly see the key influence of the selection, proportioning and process innovation of each element in the present invention on the performance of the alloy, providing a solid basis for in-depth understanding and application of the invention.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A nanocomposite tungsten-based alloy, characterized in that: The alloy comprises the following components in parts by weight: W powder: 84.0-87.0 parts, Ni powder: 7.0-9.0 parts, Fe powder: 3.0-5.0 parts, Co powder: 0.2-0.5 parts, Mo powder: 1.5-2.5 parts, Zr powder: 0.8-1.0 parts, Cr powder: 0.5-0.8 parts, Mn powder: 0.3-0.5 parts, B powder: 0.4-0.5 parts, Ta powder: 0.2-0.4 parts, Hf powder: 0.1-0.3 parts, V powder: 0.1-0.2 parts, Ti powder: 0.1-0.3 parts, silicon carbide powder: 0.1-0.2 parts, aluminum nitride powder: 0.1-0.2 parts, yttrium oxide powder: 0.3-0.5 parts, lanthanum oxide powder: 0.1-0.2 parts.

2. The nanocomposite tungsten-based alloy according to claim 1, characterized in that: The mass ratio of the silicon carbide powder to the lanthanum oxide powder is 1:0.6-0.

9.

3. The nanocomposite tungsten-based alloy according to claim 1, characterized in that: The total mass of the Ti powder, Ta powder and Co powder accounts for 0.7-0.95% of the alloy.

4. The nanocomposite tungsten-based alloy according to claim 1, characterized in that: The Fischer particle size of the W powder is 2.0-4.0 μm; the Fischer particle size of the Ni powder is 2.0-4.0 μm; the Fischer particle size of the Fe powder is 5.0-8.0 μm; the Fischer particle size of the Co powder is 1.0-3.0 μm; the Fischer particle size of the Mo powder is 2.0-5.0 μm; the Fischer particle size of the Cr powder is 1.5-4.0 μm; the Fischer particle size of the Mn powder is 5.0-6.0 μm; the Fischer particle size of the B powder is 1.5-3.0 μm; The Fischer-Strauss particle size of the Ta powder is 0.5-1.0 μm; the Fischer-Strauss particle size of the Hf powder is 0.5-1.0 μm; the Fischer-Strauss particle size of the V powder is 1.0-2.0 μm; the Fischer-Strauss particle size of the Ti powder is 1.0-2.0 μm; the Fischer-Strauss particle size of the silicon carbide powder is 50-200 nm; the Fischer-Strauss particle size of the aluminum nitride powder is 50-200 nm; the Fischer-Strauss particle size of the yttrium oxide powder is 2.0-4.0 μm; and the Fischer-Strauss particle size of the lanthanum oxide is 2.0-4.0 μm.

5. The method for preparing the nanocomposite tungsten-based alloy according to any one of claims 1 to 4, characterized in that: The steps include: (1) putting each component into a multi-stage powder mixing device for preliminary mixing to obtain a mixed powder; (2) placing the mixed powder into an elastic mold for cold isostatic pressing to obtain a rod blank; (3) The rod blank is subjected to low-temperature activation sintering, forging, annealing, and low-temperature aging treatment to obtain the nano-composite tungsten-based alloy.

6. The method for preparing the nanocomposite tungsten-based alloy according to claim 5, characterized in that: The multi-stage powder mixing equipment in step (1) has a rotation speed of 1000-1500 rpm, a vibration frequency of 10-20 Hz, and a time of 8-15 hours.

7. The method for preparing the nanocomposite tungsten-based alloy according to claim 5, characterized in that: The pressure of the cold isostatic pressing step in step (2) is 150-250 MPa, and the holding time is 5-10 min.

8. The method for preparing the nanocomposite tungsten-based alloy according to claim 5, characterized in that: The low-temperature activated sintering step in the step (3) is assisted by ultrasound, the frequency of the ultrasound is 35-75kHz, the power is 1.5-4kW, the time of the heating stage is 1.5-2.5h, the time of the insulation stage is 2-3h, and the time of the cooling stage is 0.5-1h; the temperature of the low-temperature activated sintering step is 1050-1250°C, the time is 4-6h, the heating rate is 8-12°C / min, the activator is yttrium oxide or lanthanum oxide, and the addition amount of the activator is 1-2.5wt%.

9. The method for preparing the nanocomposite tungsten-based alloy according to claim 5, characterized in that: The temperature of the forging step in step (3) is 450-900°C, the heat preservation time is 0.8-2.2h, the forging passes are 3-5 times, and the forging amount each time does not exceed 25%; the temperature of the low-temperature aging treatment step in step (3) is 200-300°C, the heat preservation time is 1-2h.

10. The method for preparing the nanocomposite tungsten-based alloy according to claim 5, characterized in that: The annealing step in step (3) includes preheating treatment and vacuum pulse annealing; the preheating temperature is 300-400°C, and the preheating time is 0.5-1h; the vacuum pulse annealing includes heating annealing and pulse cooling process; the vacuum degree of heating annealing is 10 -4 -10 - 5 Pa; the heating process of vacuum pulse annealing is divided into the following stages: heating from room temperature to 600℃, with a heating rate of 5-8℃ / min; heating from 600℃ to 900℃, with a heating rate of 8-12℃ / min; heating from 900℃ to 1050-1150℃, with a heating rate of 6-10℃ / min; a 10-15min constant temperature platform period is set at the end of each heating stage; the cooling process of vacuum pulse annealing adopts pulse cooling method: when cooling to 700℃, first quickly cool to 800℃, with a cooling rate of 8-10℃ / min, keep for 5-10min, and then slowly cool to 700℃, with a cooling rate of 3-5℃ / min; when cooling from 700℃ to 300℃, first quickly cool to 500℃, with a cooling rate of 6-8℃ / min, and then slowly cool to 300℃, with a cooling rate of 2-4℃ / min; finally cool from 300℃ to room temperature, with a cooling rate of 5-8℃ / min, and a vacuum degree of 10 -5 -10 -6 Pa and maintain for 3-5min.

Citation Information

Cited By

  • Aluminum-tungsten-copper multi-component alloy and preparation method thereof

    CN120443020A

  • Aluminum-tungsten-copper multi-component alloy and method for producing the same

    CN120443020B